In‐Depth Microstructural Evolution Analyses of Cement‐Bonded Spinel Refractory Castables: Novel Insights Regarding Spinel and CA 6 Formation - Sako, Eric Y.; Braulio, Mariana A. L.; Zinngrebe, Enno; van der Laan, Sieger R.; Pandolfelli, Victor C. (Journal of the American Ceramic Society, 2012)
Calcium hexaluminate ( CaO ·6 Al 2 O 3 – CA 6 ) is usually associated as the product reaction between alumina and CA 2 ( CaO ·2 Al 2 O 3 ) in cement‐bonded refractory castables. However, some investigations related to the Al 2 O 3 – CaO – MgO ternary system have indicated that CA 6 could be generated by additional routes, involving two other high‐alumina phases: CaMg 2 Al 16 O 27 ( CM 2 A 8 ) and Ca 2 Mg 2 Al 28 O 46 ( C 2 M 2 A 14 ). Considering the lack of conclusive studies on this subject in the refractories field, the present study addresses an in‐depth microstructural evolution analysis of high‐alumina castables containing in situ or preformed spinel ( MgAl 2 O 4 ) in order to check the actual CA 6 development steps in the presence of an MgO ‐containing phase. By scanning electron microscopy ( SEM ) and thermodynamic calculations, it was observed that CA 6 formation took place indeed as a result of the decomposition reaction of CM 2 A 8 , which was firstly generated due to the interaction between spinel and Al 2 O 3 – CaO – Na 2 O – SiO 2 liquid. Although, the results confirmed this complex CA 6 formation route regardless of the spinel incorporation method (pre‐formed grains addition or in situ reaction), the CA 6 crystals distribution after the thermal treatment was entirely affected by the previous spinel grains location. Those different microstructural profiles could be the conclusive aspects to explain the poorer slag resistance of preformed spinel‐containing castables when in contact with steel ladle slags.